Ancient Schwannoma-A Rare Case - Shilpa, B (Research and Publications Office of Jimma University, 2012)
Schwannoma is a relatively uncommon, slow-growing benign tumor that is derived apparently from the Schwann cells lining the nerve sheath. The schwannoma is usually a solitary lesion, and can be multiple when associated with neurofibromatosis. A case of 40-year-old women with a swelling in her mid-portion of the lower lip is presented. The diagnosis was established based on clinical, histopathological, and immunohistochemical aspects.